Spatial multiomics map of trophoblast development in early pregnancy - Arutyunyan, Anna; Roberts, Kenny; Troulé, Kevin; Wong, Frederick C. K.; Sheridan, Megan A.; Kats, Ilia; Garcia-Alonso, Luz; Velten, Britta; Hoo, Regina; Ruiz-Morales, Elias R.; Sancho-Serra, Carmen; Shilts, Jarrod; et al. (Nature (London), 2023)
The relationship between the human placenta—the extraembryonic organ made by the fetus, and the decidua—the mucosal layer of the uterus, is essential to nurture and protect the fetus during pregnancy. Extravillous trophoblast cells (EVTs) derived from placental villi infiltrate the decidua, transforming the maternal arteries into high-conductance vessels 1 . Defects in trophoblast invasion and arterial transformation established during early pregnancy underlie common pregnancy disorders such as pre-eclampsia 2 . Here we have generated a spatially resolved multiomics single-cell atlas of the entire human maternal–fetal interface including the myometrium, which enables us to resolve the full trajectory of trophoblast differentiation. We have used this cellular map to infer the possible transcription factors mediating EVT invasion and show that they are preserved in in vitro models of EVT differentiation from primary trophoblast organoids 3 , 4 and trophoblast stem cells 5 . We define the transcriptomes of the final cell states of trophoblast invasion: placental bed giant cells (fused multinucleated EVTs) and endovascular EVTs (which form plugs inside the maternal arteries). We predict the cell–cell communication events contributing to trophoblast invasion and placental bed giant cell formation, and model the dual role of interstitial EVTs and endovascular EVTs in mediating arterial transformation during early pregnancy. Together, our data provide a comprehensive analysis of postimplantation trophoblast differentiation that can be used to inform the design of experimental models of the human placenta in early pregnancy. A multiomics single-cell atlas of the human maternal–fetal interface including the myometrium, combining spatial transcriptomics data with chromatin accessibility, provides a comprehensive analysis of cell states as placental cells infiltrate the uterus during early pregnancy.